Improvement of Economic Mechanisms for State Regulation of Innovative Activities - Madina Kamilovna, Abdullayeva; Dilnozakhon Barnaevna, Odilova; Shakhnoza Adkhamovna, Begmatova; Doston Turgunovich, Turgunov; Latofat Sadullayevna, Karimova (International Journal of Psychosocial Rehabilitation, 2020)
The main directions of innovation policy of the state, tactical and strategic types of innovation policy, direct and indirect methods of regulation of international relations, and innovations in the field of innovation activity. Administrative and program-targeted methods. Experience of the USA, Japan, and European countries on the regulation of credit and tax incentives and innovation.